THE ROLE OF HUMAN CAPITAL IN IMPLEMENTING INNOVATIONS IN THE AGRICULTURAL SECTOR - Syrotiuk , Г.; Boltianska , Л. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The study focuses on the impact of human capital on the implementation of innovations in the agricultural sector. It emphasizes the importance of modern technologies and innovations in improving production efficiency, reducing environmental impact, and ensuring the competitiveness of agricultural products in the international market. The successful implementation of these innovations depends on the availability and effective use of human capital. The research identifies the main elements for the development of human capital in the agricultural sector and highlights the key properties of human capital that stimulate innovative development and enhance the sector's competitiveness. The study emphasizes the need for agricultural enterprises to quickly adapt to new technologies and address issues that arise during the implementation of innovations. It also highlights the importance of key components of human capital, including knowledge and skills, experience, education and training, creative potential, adaptability and flexibility, as well as communication skills and collaboration, especially in the context of contemporary challenges for agriculture such as climate change and environmental issues. The study underlines the significance of investing in human capital development as a strategic direction for ensuring the sustainable development of the agricultural sector and discusses the interrelationship between human capital and innovations. It also proposes directions for improving the quality of human capital in the agricultural sector, such as developing professional education and training systems, creating qualification enhancement and retraining programs, implementing motivational mechanisms for attracting and retaining talented workers, and expanding cooperation with scientific institutions to integrate the latest scientific achievements into agricultural practices.